A high-toughness corrosion-resistant nickel-chromium-based alloy electrode, a preparation method and application thereof

CN118305489BActive Publication Date: 2026-10-27HARBIN WELL WELDING CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410413625.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-08
Publication Date
2026-10-27
Estimated Expiration
2044-04-08

AI Technical Summary

Technical Problem

随着多晶硅制造的高速发展,冷氢化流化床反应器的制造需求也随之激增,然而其配套焊条主要依赖进口,若完全依赖于进口则周期长效率低

Benefits of technology

(1)本发明通过在药皮中添加多种熔点的碳酸盐,如碳酸钙、碳酸钡和碳酸锰,加大电弧吹力,提高电弧的稳定性;不同熔点的氟化物,如氟化钙和氟化钾,为熔渣提供了适当的流动性;添加适量氧化钛,提高电弧稳定性,改善焊缝成型。除此之外更重要的是,严格控制碳酸盐、氟化物和氧化物的比例,调整熔渣地黏度和表面张力,从而使焊条达到最优的全位置焊工艺性。此外,本发明通过设计适当的焊条外径与焊芯直径之间的距离,将焊条外径与焊芯直径的差控制在2-3mm之间,优选地,控制在2.2-2.8mm之间,使焊条套筒长短适宜,实现焊条的全位置焊。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118305489B_ABST
    Figure CN118305489B_ABST
Patent Text Reader

Abstract

A kind of high-toughness corrosion-resistant nickel-chromium base alloy electrode for polycrystalline silicon preparation key equipment and its preparation method and application.The present application belongs to the field of electrode and its preparation.The electrode of the present application is composed of a welding core and a coating.The welding core is composed of the following components in percentage by mass:C:0.06-0.10%, Si:0.10-0.30%, Mn:0.5-1.5%, S:≤0.008%, P:≤0.010%, Cr:20.5-25.0%, Fe:13.0-17.0%, Mo:5.0-9.0%, W+Co:≤2.0%, Al+Ti:≤0.5%, Cu:≤0.1%, Ce:0.01-0.05%, Y:0.01-0.05%, Ni:balance.The coating adopts CaO-BaO-CaF2-TiO2 low-hydrogen slag system.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of welding electrodes and their preparation, specifically relating to a high-toughness and corrosion-resistant nickel-chromium-based alloy welding electrode, its preparation method, and its application. Background Technology

[0002] Developing the photovoltaic industry requires not only the development of high-purity, low-cost polycrystalline silicon materials, but also improving the conversion rate of the byproduct silicon tetrachloride to achieve closed-loop polycrystalline silicon production. Hydrochlorination technology is an effective way to achieve this. The cold hydrogenation fluidized bed reactor, as a key piece of equipment in hydrochlorination technology, completes the entire fluidization reaction through high-temperature, high-pressure gas flow. The reactor should possess characteristics such as high temperature resistance, high pressure resistance, and corrosion resistance.

[0003] The main materials for cold hydrogenation fluidized bed reactors are divided into three generations, primarily including UNS N06002, UNS N08810, and UNS N08120 alloys. Among them, UNS N08120 alloy, due to its excellent high-temperature performance, can meet the requirements of large-scale and lightweight polysilicon manufacturing equipment and has become the material of choice for the new generation of cold hydrogenation reactors. With the rapid development of polysilicon manufacturing, the manufacturing demand for cold hydrogenation fluidized bed reactors has also surged. However, its matching welding electrodes mainly rely on imports, which results in long lead times and low efficiency. The main difficulties in developing matching welding electrodes include: welding processability that matches the base materials such as UNS N08120 alloys; unsatisfactory high-temperature mechanical properties (striving for a yield strength ≥300MPa at 600℃ and an elongation after fracture ≥35%) and corrosion resistance (striving for a corrosion rate ≤3mm / a after a 120-hour corrosion test according to ASTM G28 A method); and the susceptibility to hot cracking during welding. Summary of the Invention

[0004] To overcome the shortcomings of the existing technology, the present invention provides a high-toughness and corrosion-resistant nickel-chromium-based alloy welding electrode, its preparation method and application. The welding electrode has good all-position welding processability, excellent high-temperature mechanical properties, corrosion resistance and excellent resistance to hot cracking, and is applied to the preparation of a new generation of cold hydrogenated fluidized bed reactors.

[0005] The technical solution of the present invention is achieved in the following ways: One objective of this invention is to provide a high-toughness and corrosion-resistant nickel-chromium-based alloy welding electrode, which consists of a core and a coating. The core, by mass percentage, comprises the following: C: 0.06–0.10%, Si: 0.10–0.30%, Mn: 0.5–1.5%, S: ≤0.008%, P: ≤0.010%, Cr: 20.5–25.0%, Fe: 13.0–17.0%, Mo: 5.0–9.0%, W+Co: ≤2.0%, Al+Ti: ≤0.5%, Cu: ≤0.1%, Ce: 0.01–0.05%, Y: 0.01–0.05%, Ni: balance. The coating uses a CaO-BaO-CaF2-TiO2 low-hydrogen slag system.

[0006] Further specifying, the composition of the drug coating by mass percentage is as follows: calcium carbonate: 20-30%, barium carbonate: 15-30%, manganese carbonate: 1-5%, calcium fluoride: 10-30%, potassium fluoride: 2-10%, titanium oxide: 8-15%, iron powder: 5-15%, electrolytic manganese: 0.5-3%, metallic chromium: 2-5%, molybdenum powder: 0.5-5%, rare earth ferrosilicon: 0.5-2.0%, aluminum-magnesium alloy: 0.5-1.5%, lanthanum oxide: 0.1-0.5%, sodium carbonate: 0.5-1%, and the ratio of carbonate to (oxide + fluoride) is 0.8-1.7.

[0007] Further specifying the rare earth ferrosilicon composition: La: 13-14%, Ce: 12-13%, Mn: 2-3%, Ti: 1-2%, Si: 42-43%, with Fe as the balance.

[0008] A second objective of this invention is to provide a method for preparing the aforementioned nickel-chromium-based alloy welding electrode, the method comprising: After the coating powder is mixed evenly, the binder is added and the mixture is stirred and mixed thoroughly. Then, it is pressed onto the welding core and baked at a low temperature first, followed by baking at a high temperature to obtain the welding rod.

[0009] Further specified, the mass of the binder is 20-30% of the total mass of the drug coating powder.

[0010] Further specified, the pressure for pressure coating is 10-20 MPa.

[0011] Further specify that the low-temperature baking temperature is 100-150℃ and the time is 1-3 hours.

[0012] Further specified, the high-temperature baking temperature is 300-400℃, and the time is 1-3 hours.

[0013] The third objective of this invention is to provide a deposited metal for the above-mentioned nickel-chromium-based alloy welding electrode, which, by mass percentage, comprises the following: C: 0.06–0.10%, Si: 0.2–0.4%, Mn: 1.0–1.5%, S: ≤0.010%, P: ≤0.010%, Cr: 22.0–25.0%, Mo: 7.0–9.5%, Fe: 17.0–18.0%, W+Co: ≤1.5%, Al+Ti: ≤0.1%, Cu: ≤0.1%, Ni: balance.

[0014] The fourth objective of this invention is to provide an application of the aforementioned nickel-chromium-based alloy welding electrode, which is used to prepare a cold hydrogenated fluidized bed reactor.

[0015] Compared with existing inventions, the present invention has the following beneficial effects: (1) This invention increases the arc blowing force and improves the stability of the arc by adding carbonates with various melting points, such as calcium carbonate, barium carbonate, and manganese carbonate, to the coating; fluorides with different melting points, such as calcium fluoride and potassium fluoride, provide appropriate fluidity for the slag; and adding an appropriate amount of titanium oxide improves arc stability and weld formation. More importantly, it strictly controls the proportions of carbonates, fluorides, and oxides to adjust the viscosity and surface tension of the slag, thereby achieving optimal all-position welding processability of the electrode. In addition, this invention designs an appropriate distance between the outer diameter of the electrode and the diameter of the core, controlling the difference between the outer diameter of the electrode and the diameter of the core to be between 2-3 mm, preferably between 2.2-2.8 mm, so that the length of the electrode sleeve is appropriate, realizing all-position welding of the electrode.

[0016] (2) This invention effectively reduces the resistivity of the welding core by adding a large amount of iron powder to the flux coating, ensuring that the welding electrode does not exhibit a red tail phenomenon under high current. The addition of electrolytic manganese, rare earth ferrosilicon, metallic chromium, and molybdenum powder to the flux coating primarily serves deoxidation and transition alloying, rationally controlling the composition of alloying elements in the electrode's deposited metal to achieve the optimal strength-toughness ratio and corrosion resistance of the weld, especially maintaining good strength and toughness even at 600℃. Adding a certain amount of aluminum-magnesium alloy to the flux coating can pre-deoxidize, significantly reducing the oxidizing atmosphere of the arc and facilitating the precipitation of rare earth active atoms.

[0017] (3) Adding a certain amount of lanthanum oxide to the coating allows rare earth oxides to decompose at high temperatures during the droplet stage and adsorb onto the droplets. These oxides then transition into the molten pool, where they combine with sulfur to desulfurize and purify the pool, effectively reducing the tendency for hot cracking in the weld. Simultaneously, it reduces the oxygen content in the deposited metal, inhibits the formation of irregular inclusions, and creates dispersed spherical inclusions, thereby improving the toughness of the electrode deposited metal.

[0018] (4) Based on the traditional use of alloy welding core, the present invention innovatively uses non-alloy nickel-chromium iron welding core and adds a large amount of iron powder to the coating, which effectively improves the flat and vertical welding process of the welding electrode and the pressure coating of the welding electrode.

[0019] (5) This invention aims to minimize the hot cracking tendency of nickel-chromium-molybdenum welding electrodes by employing multiple measures. First, the purity of the flux coating raw materials is strictly controlled, controlling the content of S, P, B, Zr, etc. in the deposited metal from the source, thereby reducing the tendency of the weld to hot crack. Second, appropriate amounts of rare earth elements are added to both the core and the flux coating to desulfurize, reduce oxygen, and purify the molten pool, effectively reducing the tendency of the weld to hot crack. Third, the Mo content in the electrode deposited metal is controlled, as welding hot cracking is related to the segregation of Mo. The results show that no hot cracking tendency was observed in the weld metal of a 60mm thick UNS N08120 alloy butt joint test plate.

[0020] (6) Low Si and high Cr content can improve the corrosion resistance of the alloy in oxidizing corrosive media and enhance its resistance to localized corrosion; high Mo content can improve the alloy's resistance to chloride intergranular corrosion (SCC). This invention strictly controls the Si content in the electrode deposited metal to 0.2–0.4% and rationally controls the C, Cr, and Mo content in the deposited metal, ensuring that the electrode deposited metal retains high toughness at 600℃ while also exhibiting excellent corrosion resistance. Results show that the yield strength of the electrode deposited metal at 600℃ is ≥300MPa, reaching 350MPa. A 120-hour corrosion test according to ASTM G28 A method shows a corrosion rate of approximately 1.3 mm / a, meeting engineering design requirements.

[0021] (7) This invention provides a novel nickel-based alloy welding electrode for the preparation of a key piece of equipment for polycrystalline silicon—the cold hydrogenation fluidized bed reactor. Attached Figure Description

[0022] Figure 1 The performance of the bevel flat welding process using the welding electrode of Example 1; Figure 2 The performance of the bevel flat welding process using the welding electrode of Example 2; Figure 3 The performance of the bevel flat welding process using the welding electrode of Example 3; Figure 4 The macroscopic morphology of a 60mm thick UNS N08120 alloy butt joint welded using the welding rod of Example 3; Figure 5 The tensile fracture surface microstructure of a 60mm thick UNS N08120 alloy butt joint welded using welding rods from Example 3 is shown. Detailed Implementation

[0023] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention.

[0024] Unless otherwise specified, the experimental methods used in the following examples are conventional methods. Unless otherwise specified, the materials, reagents, methods, and instruments used are all conventional materials, reagents, methods, and instruments in the art, and can be obtained commercially by those skilled in the art.

[0025] The raw materials used in the following examples are: calcium carbonate (CaCO3≥96%), barium carbonate (BaCO3≥98.5%), manganese carbonate (MnCO3≥99.5%), calcium fluoride (CaF≥98%), potassium fluoride (KF≥98%), titanium oxide (TiO2≥98%), iron powder (Fe≥99.5%), electrolytic manganese (Mn≥99.5%), metallic chromium (Cr≥99.5%), molybdenum powder (Mo≥99.5%), rare earth ferrosilicon (La: 13.6%, Ce: 12.4%, Mn: 2.7%, Ti: 1.8%, Si: 42.3%, Fe: balance), aluminum-magnesium alloy (Al+Mg≥97%, of which Al: 51.7%, Mg: 47.8%), lanthanum oxide (La2O3≥99.5%), and sodium carbonate (Na2CO3≥99.5%).

[0026] Example 1: The high-toughness and corrosion-resistant nickel-chromium based alloy welding electrode in this embodiment consists of a core and a coating. The core diameter is 4.0 mm. The core composition by weight percentage is as follows: C: 0.080%, Si: 0.10%, Mn: 0.6%, S: 0.005%, P: 0.007%, Cr: 20.8%, Fe: 14.0%, Mo: 8.5%, W: 0.5%, Co: 0.7%, Al: 0.1%, Ti: 0.2%, Cu: 0.08%, Ce: 0.01%, Y: 0.02%, Ni: balance. For details, please refer to Table 1. The coating uses a CaO-BaO-CaF2-TiO2 low-hydrogen slag system, and its composition by mass percentage is as follows: calcium carbonate: 20%, barium carbonate: 20%, manganese carbonate: 1%, calcium fluoride: 13%, potassium fluoride: 9%, titanium oxide: 13%, iron powder: 14.5%, electrolytic manganese: 1.5%, metallic chromium: 3.5%, molybdenum powder: 1%, rare earth ferrosilicon: 1.0%, aluminum-magnesium alloy: 1.0%, lanthanum oxide: 0.5%, sodium carbonate: 1.0%. For details, please refer to Table 2.

[0027] The preparation method of the welding electrode is as follows: Mix the flux powder evenly, add 25% of the total mass of the flux powder with potassium sodium water glass (potassium sodium ratio of 3:1) as a binder, continue to stir and mix evenly, then press the flux onto the welding core with a pressure of 15MPa on a pressure coating machine, then bake at a low temperature of 150℃ for 2 hours, and then bake at a high temperature of 350℃ for 2 hours to obtain a welding electrode with a diameter of 6.8mm. The composition of the weld metal of the welding electrode is detailed in Table 3.

[0028] Welding test plates for mechanical properties of the deposited metal were performed according to the process parameters in Table 4. The bevel type was a 60° butt joint, the root gap was 13mm, and the test plate size was 400mm×300mm×20mm. Processability details are shown in Table 4. Figure 1 As shown, the arc is stable, the weld bead has fine ripples, minimal spatter, and is easy to remove slag. The test results of the electrode deposited metal properties are shown in Table 5.

[0029] Example 2: The high-toughness and corrosion-resistant nickel-chromium based alloy welding electrode in this embodiment consists of a core and a coating. The core diameter is 3.2 mm. The core composition by weight percentage is as follows: C: 0.075%, Si: 0.20%, Mn: 0.7%, S: 0.006%, P: 0.008%, Cr: 21.0%, Fe: 15.0%, Mo: 8.7%, W: 0.6%, Co: 0.7%, Al: 0.1%, Ti: 0.3%, Cu: 0.05%, Ce: 0.03%, Y: 0.03%, Ni: balance. For details, please refer to Table 1. The coating uses a CaO-BaO-CaF2-TiO2 low-hydrogen slag system, and its composition by mass percentage is as follows: calcium carbonate: 25%, barium carbonate: 18%, manganese carbonate: 3%, calcium fluoride: 15%, potassium fluoride: 7%, titanium oxide: 12%, iron powder: 12%, electrolytic manganese: 1%, metallic chromium: 2.5%, molybdenum powder: 1.5%, rare earth ferrosilicon: 1.0%, aluminum-magnesium alloy: 0.8%, lanthanum oxide: 0.4%, sodium carbonate: 0.8%. For details, please refer to Table 2.

[0030] The preparation method of the welding electrode is as follows: Mix the flux powder evenly, add 25% of the total mass of the flux powder with potassium sodium water glass (potassium sodium ratio of 3:1) as a binder, continue to stir and mix evenly, then press the flux onto the welding core with a pressure of 15MPa on a pressure coating machine, then bake at a low temperature of 150℃ for 2 hours, and then bake at a high temperature of 350℃ for 2 hours to obtain a welding electrode with a diameter of 5.4mm. The composition of the deposited metal of the welding electrode is detailed in Table 3.

[0031] Welding test plates for mechanical properties of the deposited metal were performed according to the process parameters in Table 4. The bevel type was a 60° butt joint, the root gap was 7mm, and the test plate size was 400mm×300mm×20mm. See Table 4 for process properties. Figure 2As shown, the arc is stable, the weld bead has fine ripples, minimal spatter, and is easy to remove slag. The test results of the electrode deposited metal properties are shown in Table 5.

[0032] Example 3: The high-toughness and corrosion-resistant nickel-chromium based alloy welding electrode in this embodiment consists of a core and a coating. The core diameter is 4.0 mm. The core composition by weight percentage is as follows: C: 0.070%, Si: 0.15%, Mn: 0.8%, S: 0.005%, P: 0.006%, Cr: 21.5%, Fe: 15.5%, Mo: 9.0%, W: 0.5%, Co: 1.0%, Al: 0.2%, Ti: 0.2%, Cu: 0.06%, Ce: 0.05%, Y: 0.04%, Ni: balance. For details, please refer to Table 1. The coating uses a CaO-BaO-CaF2-TiO2 low-hydrogen slag system, and its composition by mass percentage is as follows: calcium carbonate: 23%, barium carbonate: 16%, manganese carbonate: 5%, calcium fluoride: 14%, potassium fluoride: 10%, titanium oxide: 15%, iron powder: 11%, electrolytic manganese: 0.5%, metallic chromium: 2%, molybdenum powder: 0.5%, rare earth ferrosilicon: 1.0%, aluminum-magnesium alloy: 1.0%, lanthanum oxide: 0.3%, sodium carbonate: 0.7%. For details, please refer to Table 2.

[0033] The preparation method of the welding electrode is as follows: Mix the flux powder evenly, add 25% of the total mass of the flux powder with potassium sodium water glass (potassium sodium ratio of 3:1) as a binder, continue to stir and mix evenly, then press the flux onto the welding core with a pressure of 15MPa on a pressure coating machine, then bake at a low temperature of 150℃ for 2 hours, and then bake at a high temperature of 350℃ for 2 hours to obtain a welding electrode with a diameter of 6.8mm. The composition of the weld metal of the welding electrode is detailed in Table 3.

[0034] Welding test plates for mechanical properties of the deposited metal were performed according to the process parameters in Table 4. The bevel type was a 60° butt joint, the root gap was 13mm, and the test plate size was 400mm×300mm×20mm. Processability details are shown in Table 4. Figure 3 As shown, the arc is stable, the weld bead has fine ripples, minimal spatter, and is easy to remove slag. The test results of the electrode deposited metal properties are shown in Table 5.

[0035] Table 1. Chemical composition of the welding core in welding electrodes of Examples 1-3 (mass percentage, %)

[0036] Table 2 Composition of the flux coating in welding electrodes of Examples 1-3 (mass percentage, %)

[0037] Table 3 Chemical composition of weld metal deposited by welding electrodes in Examples 1-3 (mass percentage, %)

[0038] Table 4 Welding process parameters for Examples 1-3

[0039] Table 5 Results of electrode deposited metal properties in Examples 1-3

[0040] Using the welding electrode from Example 3, with 60mm thick UNS N08120 alloy as the base material, simulating actual working conditions, an upper U-shaped bevel and a lower V-shaped bevel were used. The intermediate assembly spacing was 2.5mm, the U-shaped bevel height was 38mm, and the V-shaped bevel height was 22mm. A total of 26 layers were welded. Macroscopic metallographic analysis of the welded joint is shown below. Figure 4 As shown, no cracks were found; the tensile fracture morphology is shown in [reference needed]. Figure 5 As shown, no cracks were found, and the morphology is typical of dimples, indicating excellent resistance to hot cracking.

[0041] The above description is merely a preferred embodiment of the present invention. These specific embodiments are different implementations based on the overall concept of the present invention, and the scope of protection of the present invention is not limited thereto. Any variations or substitutions that can be easily conceived by those skilled in the art within the scope of the technology disclosed in the present invention should be included within the scope of protection of the present invention. Therefore, the scope of protection of the present invention should be determined by the scope of the claims.

Claims

1. A high-toughness and corrosion-resistant nickel-chromium-based alloy welding electrode, characterized in that, The welding electrode consists of a core and a coating. The core, by weight percentage, comprises: C: 0.06–0.10%, Si: 0.10–0.30%, Mn: 0.5–1.5%, S: ≤0.008%, P: ≤0.010%, Cr: 20.5–25.0%, Fe: 13.0–17.0%, Mo: 5.0–9.0%, W+Co: ≤2.0%, Al+Ti: ≤0.5%, Cu: ≤0.1%, Ce: 0.01–0.05%, Y: 0.01–0.05%, Ni: balance. The coating uses a CaO-BaO-CaF2-TiO2 low-hydrogen slag system. The coating, by weight percentage, comprises: calcium carbonate: 20-30%, barium carbonate: 15-30%, manganese carbonate: 1-5%, calcium fluoride: 10-30%, potassium fluoride: 2-10%, titanium oxide: 8-15%, iron powder: 5-15%, electrolytic manganese: 0.5-3%, metallic chromium: 2-5%, molybdenum powder: 0.5-5%, rare earth ferrosilicon: 0.5-2.0%, aluminum-magnesium alloy: 0.5-1.5%, lanthanum oxide: 0.1-0.5%, sodium carbonate: 0.5-1%, and carbonate / (oxide + fluoride) = 0.8-1.

7.

2. The welding electrode according to claim 1, characterized in that, Rare earth ferrosilicon contains: La: 13-14%, Ce: 12-13%, Mn: 2-3%, Ti: 1-2%, Si: 42-43%, and Fe as the balance.

3. The method for preparing the nickel-chromium based alloy welding electrode according to any one of claims 1-2, characterized in that, The method includes: After the coating powder is mixed evenly, the binder is added and the mixture is stirred and mixed thoroughly. Then, it is pressed onto the welding core and baked at a low temperature first, followed by baking at a high temperature to obtain the welding rod.

4. The method according to claim 3, characterized in that, The binder accounts for 20-30% of the total mass of the drug coating powder.

5. The method according to claim 3, characterized in that, The pressure for pressure coating is 10-20 MPa.

6. The method according to claim 3, characterized in that, Low-temperature baking is performed at a temperature of 100–150℃ for 1–3 hours.

7. The method according to claim 3, characterized in that, The high-temperature baking temperature is 300-400℃, and the time is 1-3 hours.

8. The deposited metal of the nickel-chromium based alloy welding electrode according to any one of claims 1-2, by mass percentage, comprises the following: C: 0.06-0.10%, Si: 0.2-0.4%, Mn: 1.0-1.5%, S: ≤0.010%, P: ≤0.010%, Cr: 22.0-25.0%, Mo: 7.0-9.5%, Fe: 17.0-18.0%, W+Co: ≤1.5%, Al+Ti: ≤0.1%, Cu: ≤0.1%, Ni: balance.

9. The application of the nickel-chromium based alloy welding electrode according to any one of claims 1-2 in the preparation of a cold hydrogenated fluidized bed reactor.

Citation Information

Patent Citations

  • Nickel-based welding electrode matched with 9Ni steel

    CN102500951A

  • Nickel-based welding rod for welding nickel chromium iron alloy steel

    CN102922168A